PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS CANVA DAN ZEP QUIZ PADA MATERI FPB DAN KPK UNTUK SISWA KELAS V SEKOLAH DASAR - Ulfah Nur Jannah, Nadia; Kartinah; Azizah, Mira (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The background of this study is the low level of student enthusiasm in participating in learning, resulting in students having difficulty understanding the concepts of the Greatest Common Factor (GCF) and Least Common Multiple (LCM). Additionally, learning activities still rely on conventional media, making it necessary to develop technology-based learning media that are more engaging and interactive. The research questions are: 1) What is the validity of interactive multimedia based on Canva and Zep Quiz for GCF and LCM material for fifth-grade elementary school students? 2) How practical is this interactive multimedia? 3) How effective is it in the learning process? The objective of this research is to determine the validity, practicality, and effectiveness of interactive multimedia based on Canva and Zep Quiz for GCF and LCM material for fifth-grade elementary school students. The research design used is Research and Development (R&D) employing the ADDIE development model, which includes the Analysis, Design, Development, Implementation, and Evaluation. The study was conducted at Tlogosari Kulon 04 State Elementary School in Semarang. The results indicate that the media’s validity level is very good, with a media expert validation rate of 96.67% and an average content expert validation rate of 97.50%. The practicality of the media was also in the very good category, as indicated by the results of the teacher response questionnaire at 98.67% and the student response at 98.57%. The effectiveness of the media was demonstrated by the N-Gain test results of 79.25%.